Seroprevalence of HIV-HBV Co-Infection - Suresh B. Sonth; Sathyanarayan M.S; Mariraj J.; Krishna S. (Al Ameen Medical College, 2012)
: Objectives: To find the rate of prevalence of Hepatitis B viral co-infection with Human Immunodeficiency virus infection and comparing its prevalence in male and female patients. Background: Chronic hepatitis B virus (HBV) infection, which affects 7%-10% of HIV-infected patients, is associated with an increased frequency of AIDS-related and non-AIDS-related clinical endpoints, such as end-stage liver diseases including cirrhosis and hepatocellular carcinoma. HIV and hepatitis B virus (HBV) infection share transmission patterns and risk factors; therefore, it is not surprising that the prevalence of chronic HBV infection is elevated among HIV-infected persons. Method: A total of 100 patients were picked up who were positive for HIV 1 & 2 antibodies (Tridot & ELISA), & tested for the presence of HBsAg (ELISA). As control, 100 healthy blood donors were tested for the presence of HBsAg. Result: Out of 100 HIV infected patients, 21 (21%) were positive for the presence of HBsAg, as compared to only 2 (2%) among healthy blood donors. Conclusion: Hence considering the high infectivity, morbidity and mortality due to HBV in HIV infected individuals, routine evaluation of hepatitis B virus markers may be carried out in all the HIV infected individuals